SOSIALISASI PENGGUNAAN APLIKASI SI ARSIP SURAT MASUK DAN KELUAR ( ARSIPARIS) DI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA BENGKULU DALAM RANGKA DIGITALISASI FILE - Rojali Toyib; Dandi Sunardi; Muntahanah Muntahanah; Nuri Vironika; Sastia Wibowo (Universitas Muhammadiyah Bengkulu, 2025)
Suboptimal archive management can negatively impact an organization's efficiency, due to wasted time searching for documents that should be quickly accessible, thus decreasing work productivity at the Bengkulu City Education and Culture Office. Archive digitization emerged as an alternative to increase effectiveness and security in document management. Archiving is understood as an institutional activity related to the processing and storage of incoming and outgoing information (such as letters, reports, and forms). Computerized systems, recording, storing, and searching for letters become faster and more accurate, reducing the possibility of document loss, and providing more flexible access for users. The conclusions from the socialization and practice of creating this Archivist application are: 1. Participants gave a very positive response to the guidance carried out by the team from the Muhammadiyah University of Bengkulu in the socialization, training, and practice of creating a library website, saying that the activity received a positive response of 95% of the total aspects asked. 2. This Archivist application greatly supports the Office in processing archive data at the Bengkulu City Education and Culture Office. 3. Additional training is needed to broaden the knowledge of both employees and operational staff to ensure orderly administration at the Bengkulu City Education and Culture Office.